Depression, Anxiety, Body Image, Sexual Functioning, and Dyadic Adjustment Associated with Dialysis Type in Chronic Renal Failure - Öyekçin, Demet Güleç; Gülpek, Demet; Sahin, Erkan Melih; Mete, Levent (International journal of psychiatry in medicine, 2012)
Objective: Depression is the most widely studied complication in dialysis patients. In patients with chronic renal failure, changes in body image are considered to be associated with invasive treatment interventions. In addition, sexual problems are common in dialysis patients. In this study, hemodialysis and peritoneal dialysis patients are investigated for depression, anxiety, body image, sexual satisfaction, and dyadic adjustment. Methods: Hemodialysis patients (n = 36), peritoneal dialysis patients (n = 54), and healthy controls (n = 30) were included in the study. All the subjects were assessed with Structured Clinical Interview for DSM-IV, Body Image Scale, Beck Depression Inventory, Beck Anxiety Scale, Golombok-Rust Inventory for Sexual Satisfaction, and Dyadic Adjustment Scale. Results: Depression (20.64 + 15.20) and anxiety levels (14.72 + 12.36) were significantly higher in hemodialysis group compared to peritoneal dialysis (13.54 + 12.51; 12.74 + 11.21) and control groups (7.17 + 5.58; 9.86 + 9.19). In peritoneal dialysis group, as depression and anxiety levels increased, body image was disturbed and sexual satisfaction decreased. In peritoneal dialysis group, body image (86.98 + 23.63) was better than hemodialysis group (101.58 + 26.51) and was not different from the control group (83.67 + 22.11). In hemodialysis group, as depression and anxiety levels increased, body image was disturbed. In both groups, long-term dialysis disturbed body image. Conclusion: Patients should be informed about the impacts of dialysis. Clinicians may wish to monitor dialysis-users for anxiety, depression, dyadic adjustment, and body image difficulties at follow-up appointments. Interventions that target intimate partner interventions, appearance-related beliefs, and anxiety depression may be of benefit to this population.